Penggunaan Sarung Tangan Mempengaruhi Kejadian Dermatitis Kontak Iritan pada Petani Rumput Laut - Muhammad Risal (Poltekkes Kemenkes Kendari, 2020)
Irritant contact Dermatitis is an inflammation of the skin that occurs as a non-specific skin response to a chemical substance through the release of inflammatory mediators from the epidermis cells. The purpose of this research is to know the relationship of use of personal protective equipment namely gloves against the incidence of irritant contact dermatitis on seaweed farmers in the village Bawalipu, Wotu subdistrict. The study used a descriptive analytical design with cross sectional plans for respondents of 47 people. From the results of the study using Chi-square test obtained the value P = 0.05 so that it can be concluded that the use of gloves have a relationship with the incidence of irritant contact dermatitis in the seaweed farmer especially in Bawalipu village, Wotu District, so it is expected to the village government to socialize the benefits of use of gloves that one of them through cooperation with health care center.